Safety of low-density lipoprotein cholesterol reduction with atorvastatin versus simvastatin in a coronary heart disease population (the TARGET TANGIBLE Trial) - März, Winfried; Wollschläger, Helmut; Klein, Gernot; Neiß, Albrecht; Wehling, Martin (The American journal of cardiology, 1999)
Reduction in plasma lipids has been recognized as one of the primary cardiovascular risk reduction strategies in the secondary prevention of coronary heart disease (CHD). The primary end points of TARGET TANGIBLE were the safety (adverse events and laboratory measurements) and efficacy (responder rates) of therapy with atorvastatin versus simvastatin with the aim of achieving low-density lipoprotein (LDL) cholesterol lowering to ≤100 mg/dl (2.6 mmol/L). A total of 3,748 CHD patients with LDL cholesterol levels ≥130 mg/dl (3.4 mmol/L) entered a run-in diet phase of 6 weeks without any lipid-lowering drug therapy. At the end of the diet phase, 2,856 patients met the lipid criteria and were randomized to active treatment for 14 weeks. Patients received 10 to 40 mg of either drug in an optional titration design at 2:1 randomization for atorvastatin versus simvastatin. Adverse event rates were statistically equivalent (p <0.01) for simvastatin (35.7%) and for atorvastatin patients (36.3%). Both drugs were well tolerated; <5% of patients in both groups were withdrawn due to adverse events. In all, 37 atorvastatin patients (2%) and 27 simvastatin patients (3%) had serious adverse events. Drug-related side effects (elevations in creatine kinase, liver enzymes) occurred in both groups at similar rates with 10 atorvastatin patients (0.5%) and 5 simvastatin patients (0.5%) presenting confirmed transaminase elevations >3 × the upper limit of the normal range. Significantly fewer patients in the atorvastatin group (n = 724) required titration to 40 mg compared with the simvastatin group (n = 514) (38% vs 54%, respectively; p <0.001). Atorvastatin resulted in a significantly greater number of patients reaching the LDL cholesterol goal than those treated with simvastatin, with 67% of atorvastatin patients and 53% of simvastatin patients reaching the target LDL cholesterol level of ≤100 mg/dl (2.6 mmol/L) (p <0.001). Both atorvastatin and simvastatin are safe for use by patients in the secondary prevention of CHD, with patients in both drug groups having similar adverse event rates. Despite the use of concomitant medications there was no drug-induced rhabdomyolysis with either atorvastatin or simvastatin.
Gesehen am 18.10.2022